2017
DOI: 10.2217/fon-2016-0529
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with eribulin in heavily pretreated women with metastatic breast cancer: a case series

Abstract: During the last decades, much effort has been made to develop and test treatments for advanced/metastatic breast cancer (MBC) able to prolong survival and improve patients' quality of life. In this regard, eribulin represents one of the most recent and interesting discoveries. This tubulin-targeting chemotherapy demonstrated a survival benefit in MBC women who progressed after at least two prior lines of chemotherapy for the treatment of metastatic disease (prior therapies should have included an anthracycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The results of our study, in agreement with other experiences, confirm that eribulin can be active regardless of chemo- Pedersini et al therapy line [24,25] and seems to be more active in patients who received chemotherapy until progression (more than 6 cycles). In our population, eribulin showed a good tolerability profile, and patient's toxicities were acceptable and lower compared to those registered in the EMBRACE trial and in other studies [23][24][25][26][27][28][29]. This aspect deserves further consideration, as one possible reason for this lower toxicity is that eribulin chemotherapy was started at a lower dose (75%) and that 22% of the patients maintained during the whole study a reduced dosage treatment with 50% of the standard dose.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The results of our study, in agreement with other experiences, confirm that eribulin can be active regardless of chemo- Pedersini et al therapy line [24,25] and seems to be more active in patients who received chemotherapy until progression (more than 6 cycles). In our population, eribulin showed a good tolerability profile, and patient's toxicities were acceptable and lower compared to those registered in the EMBRACE trial and in other studies [23][24][25][26][27][28][29]. This aspect deserves further consideration, as one possible reason for this lower toxicity is that eribulin chemotherapy was started at a lower dose (75%) and that 22% of the patients maintained during the whole study a reduced dosage treatment with 50% of the standard dose.…”
Section: Discussionsupporting
confidence: 46%
“…Interestingly, a pooled analysis of 2 phase III studies on eribulin revealed that the OS benefit was consistent in all BC molecular subtypes, with triple-negative patients obtaining the largest benefit [22]. Eribulin activity in heavily pretreated patients in terms of ORR, CB, PFS, and OS has been further confirmed in other retrospective analyses conducted in different countries in a clinical practice setting [23][24][25][26][27][28][29]. In our experience on the use of eribulin in a real world heavily pretreated population, we observed similar outcomes to those reported in the EMBRACE trial (OS 13.5 months).…”
Section: Discussionmentioning
confidence: 80%
“…Despite the wide pharmacological armamentarium available for the treatment of MBC, long-lasting control of disease is challenging, especially in heavily pretreated patients [6][7][8]. In this case report, we documented a long-lasting CR with eribulin in a relatively young woman with MBC and bone metastasis, who did not benefit from prior chemotherapy regimens.…”
Section: Clinical Relevance and Conclusionmentioning
confidence: 88%
“…Therefore, assessment of performance of chemotherapy agents in field practice scenario helps clinicians to better apply results from clinical studies to everyday practice. To this end, it has been suggested that exploring the potential factors associated with long-lasting response to eribulin would be of the highest interest [6].…”
Section: Introductionmentioning
confidence: 99%